Analisis Hambatan Samping Di Jalan Alternatif Inspeksi Banjir Kanal Timur Terhadap Kemacetan Jalan Basuki Rahmat - Sukadi; Achmad Pahrul Rodji; Rifky Arrahman (Fakultas Teknik Universitas Krisnadwipayana, 2023)
In the land transportation system, the availability of proper and adequate infrastructure greatly affects the smoothness of traffic. The existence of small businesses along the road is a side obstacle factor that reduces road performance. This happened along the Jalan Alternatif Inspeksi Banjir Kanal Timur, there were many traders on the roadside, pedestrians, vehicles going in and out, slowing down vehicles, and parking vehicles. Vehicles that should be able to pass the Jalan Alternatif Inspeksi Banjir Kanal Timur, prefer to go through Jalan Basuki Rahmat due to congestion. This caused traffic on Jalan Basuki Rahmat to jam due to the impact of congestion on the Jalan Alternatif Inspeksi Banjir Kanal Timur. The research was conducted for 4 (four) days, namely Monday, Thursday, Saturday and Sunday (July 13-19, 2020). The research time was carried out every morning (6.30 AM to 8.30 AM), noon (11.00 AM to 1.00 PM), afternoon (5.00 PM to 7.00 PM), and evening (7 PM to 10.00 PM) with traffic volume data, vehicle speed, and side obstacles every 15 minutes for the Jalan Basuki Rahmat (direction to Jakarta) and the Jalan Alternatif Inspeksi Banjir Kanal Timur (two-way). In addition, data on the width and length of the roads under review are also taken. Further analysis was conducted with reference to the MKJI 1997. From the research results, the capacity of Jalan Basuki Rahmat (direction to Jakarta) without side obstacles is 718 pcu/hour and with side obstacles 639 pcu/hour. Meanwhile, the capacity of the Jalan Alternatif Inspeksi Banjir Kanal Timur (two-way) without side obstacles is 1452 pcu/hour and with side obstacles 1148 pcu/hour. The peak of the side obstacles on the Jalan Alternatif Inspeksi Banjir Kanal Timur occurs from the afternoon until the evening (the highest saturation degree value is 1.97 = F), at the same time there is also traffic density on Jalan Basuki Rahmat.